2023
DOI: 10.1101/2023.09.12.23295402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The variation of malaria prevention measures knowledge and their associated factors: A cross-sectional study in East Nusa Tenggara Province Indonesia

Robertus Dole Guntur,
Maria A. Kleden,
Damai Kusumaningrum
et al.

Abstract: ObjectiveMalaria is one of the major public health problems in African and Southeast Asian countries including Indonesia. However, knowledge of malaria prevention measures (MPM) is not well studied, particularly in Indonesia. This study aimed to investigate the level of MPM knowledge and associated factors among rural adults in high, moderate and low endemic settings of East Nusa Tenggara Province (ENTP) Indonesia.MethodsA community-based cross-sectional study was conducted among a randomly selected 1495 house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The recent study in the Eastern part of Indonesia, including in ENTP, indicated that the practice of various types of MPM differs among provinces [20]. Some studies on MPM had been conducted in the context of rural ENTP [21], [22], [23], [24], [25] A study on knowledge of LLINs and non-LLINs for rural community in this province indicated that rural adults in low endemic settings were knowledgeable with non-LLINs, while it was LLINs in high endemic settings [21]. Another study on Tetun ethnicity in Timor Island indicated that most of community in that group had knowledge on the traditional plants for preventing malaria [22].…”
Section: Introductionmentioning
confidence: 99%
“…The recent study in the Eastern part of Indonesia, including in ENTP, indicated that the practice of various types of MPM differs among provinces [20]. Some studies on MPM had been conducted in the context of rural ENTP [21], [22], [23], [24], [25] A study on knowledge of LLINs and non-LLINs for rural community in this province indicated that rural adults in low endemic settings were knowledgeable with non-LLINs, while it was LLINs in high endemic settings [21]. Another study on Tetun ethnicity in Timor Island indicated that most of community in that group had knowledge on the traditional plants for preventing malaria [22].…”
Section: Introductionmentioning
confidence: 99%